2004
DOI: 10.1007/s00259-004-1670-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of blood glucose level, age and fasting period on non-pathological FDG uptake in heart and gut

Abstract: Age, fasting period and blood glucose levels did not influence physiological uptake. However, there seemed to be a patient-specific pattern for stomach and bowel uptake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
56
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(59 citation statements)
references
References 3 publications
2
56
1
Order By: Relevance
“…The prevalence of this nonpathological glucose uptake is observed in up to 68% of patients who have no CDs (2).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of this nonpathological glucose uptake is observed in up to 68% of patients who have no CDs (2).…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have reported varying degrees of non-specific myocardial FDG uptake despite low blood sugar levels. De Groot et al [14] found that myocardial FDG uptake had no correlation with the fasting blood sugar level, fasting period, or age of the patient. In a similar study Kaneta et al found a negative correlation between the blood glucose level and FDG uptake, but the fasting period and age of the patient showed no relationship [15].…”
Section: Importance Of Preparation Methods For Fdg Pet/ctmentioning
confidence: 99%
“…Elimination of the uptake typically seen in the myocardium requires either a pharmacologic or a dietary intervention (41,42). Although prolonged fasting has been suggested, there is no definite evidence that this intervention reliably suppresses myocardial uptake (43)(44)(45). Further clinical testing is required to develop a method that will eliminate myocardial uptake in all patients.…”
Section: Although the Process Was Recognizedmentioning
confidence: 99%